Uji Aktivitas Antibakteri Ekstrak Etanol Dan Etil Asetat Daun Mangkokan (Polyscias scutellaria (Burm.f.) Fosberg.) Terhadap Pertumbuhan Bakteri Proteus vulgaris DAN Trichophyton mentagrophytes - Syarifah Roslianizar; Hestina; Lina Br Tarigan, Frida; Nur Putri Dewi (Universitas Sari Mutiara Indonesia, 2022)
Indonesia is a tropical country with a wide variety of plants, including the Mangkokan plant (Polyscias scutellaria (Burm.f.) Fosberg.). Mangkokan leaf (Polyscias scutellaria (Burm.f.) Fosberg.) is an ornamental or herbaceous plant. Mangkokan leaves contain compounds of alkaloids, flavonoids, saponins, and steroids/triterpenoids. These compounds are known to have antibacterial activity. The purpose of this study was to determine the antibacterial activity of the ethanolic and ethyl acetate extracts of the leaves of the Mangkukan (Polyscias scutellaria (Burm.f.) Fosberg.) against Proteus vulgaris and Trichophyton mentagrophytes bacteria and to determine the difference in the inhibition zones of the ethanol and ethyl acetate extracts of the leaves of the Mangkokan (Polyscias scutellaria (Burm.f.) Fosberg.) between the bacteria Proteus vulgaris and Trichophyton mentagrophytes. The extraction of the Mangkokan leaf was carried out by the maceration method using two solvents, ethanol 96% and ethyl acetate. The extracts obtained were screened for phytochemicals and tested for antibacterial activity against Proteus vulgaris and Trichophyton mentagrophytes using the agar diffusion method using paper discs with three repetitions and positive control administration of Ciprofloxacin and Ketoconazole. The results of the research on the diameter of the inhibition zone of the ethyl acetate extract showed the strongest antibacterial activity compared to the ethanol extract in inhibiting the growth of Proteus vulgaris and Trichophyton mentagrophytes. Antibacterial activity was tested by agar diffusion method using disc paper. Experiments using concentrations of 20%, 40%, 60%, and 80%. The difference in the zone of inhibition of the ethanol extract of the leaves of the Mangkokan (Polyscias scutellaria (Burm.f.) Fosberg.) against Proteus vulgaris bacteria was 9,4 mm, and for Trichophyton mentagrophytes it was 9,6 mm. The difference in the inhibition zone of the ethyl acetate extract of the leaves of the Mangkokan (Polyscias scutellaria (Burm.f.) Fosberg.) against Proteus vulgaris bacteria was 10,06 mm and for Trichophyton mentagrophytes it was 10,42 mm.